Core Technological Competence and Competitive Advantage: A Study on Chinese High-Tech SMEs - Tong, Tong; Iqbal, Kashif; Rahman, Azmawani Abd (Frontiers in Psychology, 2022)
This study aims to examine the effect of core technology competence on the competitive advantage of high-tech SMEs (Small and Mid-sized Enterprises in China). Based on the 379 valid responses collected from a survey, structural equation modeling (SEM) was employed to examine the research model. Infrastructure and technology, state-of-the-art technology, innovative R&D capability, and organizational flexibility all have a significant impact on the competitive advantage, while infrastructure and technology, state-of-the-art technology, and innovative R&D capability have a significant effect on organizational flexibility. Organizational flexibility plays a mediating role in innovative R&D capability’s effect on competitive advantage. Under the continuous influence of COVID-19, we should promote development from the perspective of strengthening enterprise infrastructure and technology and improving organizational flexibility to gain a competitive advantage. This study reveals the internal relationship between core technological competence, organizational flexibility, and competitive advantage. The results of this study will help us to fully understand the survival status and competitive advantage of high-tech SMEs under COVID-19.